indPOtrace: Digital Innovation for Smart Pig Farming and Safe Pork Supply Chains in India - Thomas, R; Bharadwaj, D; Kerketta, A; Sharma, D; Das, H; Gupta, V K (Journal of Meat Science, 2026)
The development of indPOtrace (Indian Pork Traceability platform) marks a significant advancement in digital infrastructure for India’s pork sector, offering a multifaceted software solution tailored to the operational, regulatory, and advisory needs of diverse stakeholders. The platform integrates distinct modules for end-to-end traceability, real time remote meat inspection, and interactive stakeholder engagement, encompassing pig producers, pork processors, traders, feed suppliers, and transporters. It enables systematic documentation of pig production and management data, including health records and farm-specific parameters, within a centralized database managed by ICAR-National Research Centre on Pig. A core innovation of indPOtrace is its remote meat inspection system trhough Meat Spec 1.0, which facilitates real-time veterinary assessment of slaughter pigs (ante-mortem) and carcasses (post-mortem) in operational abattoirs via virtual inspection protocols. The platform also houses the Opti-PigRation 1.0 module, an intelligent feed formulation tool designed to optimize the energy to-protein ratio in pig diets by farmers themselvs, particularly those incorporating unconventional feed resources. Based on Bureau of Indian Standards nutritional recommendations, the tool generates precision-guided feed suggestions for improved productivity and cost efficiency. Complementing its producer-centric features, the platform includes a consumer-facing portal enabling QR code-based traceability of pork products, fostering consumer confidence through transparent provenance data. indPOtrace thus represents a comprehensive, scalable, and intelligent system driving traceable, safe, and sustainable pork production in India.